2007
DOI: 10.1007/s00418-007-0312-8
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the glycoconjugate oligosaccharides in the human placenta from pregnancies complicated by altered glycemia: lectin histochemistry

Abstract: The aim of this study was to investigate the distribution of the oligosaccharides of the glycoconjugates in placentas from pregnancies complicated by different degree of altered glycaemia. Placentas from women with physiological pregnancies (group 1), with pregnancies complicated by minor degree of glucose intolerance (group 2) and with pregnancies complicated by gestational diabetes mellitus (GDM) treated with insulin (group 3) were collected. Ten lectins were used (ConA, WGA, PNA, SBA, DBA, LTA, UEA I, GSL I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…In pregnant women suffering altered glycaemia, major changes in placental affinity for SBA, PNA and DBA were reported (Sgambati et al. ). Also, qualitative changes in glycosylation pattern of specific placental glycoproteins between normal and missed abortion placentae were reported in humans (Serman et al.…”
Section: Discussionmentioning
confidence: 99%
“…In pregnant women suffering altered glycaemia, major changes in placental affinity for SBA, PNA and DBA were reported (Sgambati et al. ). Also, qualitative changes in glycosylation pattern of specific placental glycoproteins between normal and missed abortion placentae were reported in humans (Serman et al.…”
Section: Discussionmentioning
confidence: 99%
“…Using the mass spectrometric analysis of the glycans from these cells they obtained very similar profiles, suggesting that any changes in glycosylation most likely occur on specific proteins, rather than globally (20). In analysing the saccharide content of glycoconjugates in the human placental cells from pregnancies complicated by altered glycemia (minor degree of glucose intolerance or gestational diabetes mellitus), Sgambati et al (21) showed a decrease in the content of Sia a2,6-linked to galactose (Gal)/GlcNAc and in cre ase in GlcNAc in the placentas from pathological groups, in particular in gestational diabetes mellitus. On the other hand, the placentas from mothers with a minor degree of glucose intolerance had an increase of UEA I-reactive L-Fuc (21).…”
Section: Discussionmentioning
confidence: 99%
“…In analysing the saccharide content of glycoconjugates in the human placental cells from pregnancies complicated by altered glycemia (minor degree of glucose intolerance or gestational diabetes mellitus), Sgambati et al (21) showed a decrease in the content of Sia a2,6-linked to galactose (Gal)/GlcNAc and in cre ase in GlcNAc in the placentas from pathological groups, in particular in gestational diabetes mellitus. On the other hand, the placentas from mothers with a minor degree of glucose intolerance had an increase of UEA I-reactive L-Fuc (21). Women with pregesta tional IDDM were not examined.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, adipokines play an important role in adapting the energetic metabolism at the maternalfetal interface, and dysregulation of the receptors for these adipokines has been shown in gestational diabetes mellitus (for review, see Sgambati et al 2007). Leptin appears to be involved in embryo metabolism and may participate in embryo-maternal crosstalk, but the role of adiponectin for fertility is not clear yet.…”
Section: Female Reproductive Systemmentioning
confidence: 99%